Objective aesthetic values in art - McGorrigan, Ben D. (2015)
This dissertation defends an answer to the question: to what extent, if any, are aesthetic values in art objective? I defend what I call Moderate Aesthetic Objectivism, which can be summarised as follows. A work of art has a certain aesthetic value if and only if a human critic, in the circumstances ideal for the aesthetic experience of that work, would experience the work as having that aesthetic value. ‘Experience’ here is meant in a broad sense, encompassing imagination and understanding as well as perception. We should regard such a critic as someone who would detect the aesthetic value rather than make it the case that the work had that value. Experiencing a work as being aesthetically valuable in a certain way involves having an aesthetic experience which is itself valuable. Such an experience will be pleasurable, often in complex ways. Although critics in ideal circumstances for the aesthetic experience of a work detect aesthetic values rather than making it the case that the work has certain aesthetic values, the work only has those values because the resultant aesthetic experiences had by such critics are themselves valuable. The aesthetic values of a work are, however, realised by properties of the work which dispose it to cause such valuable aesthetic experiences for humans in the circumstances ideal for the aesthetic experience of the work. Those properties are what is aesthetically valuable in the work, and they are objective in the sense that their existence and character is independent of whether they are detected or responded to. This account therefore retains elements of both subjectivist and objectivist approaches to aesthetic value. It can, I argue, make sense of our conflicting intuitions about the objectivity or subjectivity of aesthetic values in art.